The role of right ventricular-arterial coupling in cardiac amyloidosis: a comparison between subtypes and with other genetic and non-genetic hypertrophic cardiomyopathies and prognostic consequences. (14th October 2021) - Palmiero, G; Monda, E; Rubino, M; Caiazza, M; Vetrano, E; Di Fraia, F; Lioncino, M; Dongiglio, F; Carciello, G; Manganelli, F; Ascione, L; Caso, P; et al.
Abstract: Background: Right ventricular (RV) dysfunction in cardiomyopathies is a consequence of chronic overload (i.e. aortic stenosis) or direct involvement of systemic disorders (i.e. cardiac amyloidosis, CA). The Tricuspid Annular Plane Systolic Excursion/Systolic Pulmonary Artery Pressure ratio (TAPSE/sPAP) has been recently proposed as a surrogate of RV-arterial coupling (RVAC) in many cardiac disorders. Purpose: This study aims to compare RVAC between CA subgroups and between CA and other forms of genetic and non-genetic cardiomyopathies with hypertrophic phenotype. Methods: We enrolled 50 patients with CA (26 pts with AL and 24 pts with wild type ATTR form), 75 patients with LV hypertrophy (LVH) [25 patients with HCM, 25 with hypertensive cardiomyopathy (HypCM), and 25 with aortic stenosis]. We analysed right chambers dimensions and classical and novel parameters of RV function [TAPSE, TAPSE/sPAP, St (S' wave at RV TDI), global (RVGLS) and free-wall (RVFWS) strain]. Results: The ATTR group showed higher right dimensions than AL, without differences in all RV systolic parameters (see Table 1). Compared to the LVH group, CA patients showed no differences in RV dimensions while RV systolic parameters, included the TAPSE/sPAP ratio, were significantly reduced. At ROC curve analysis TAPSE (AUC 0.877; 95% CI: 0.811–0.943; p<0, 0001) and TAPSE/sPAP ratio (AUC 0.859; 95% CI: 0.783–0.935; p<0, 0001) showed the best ability in discriminating CA among other forms of LVH (cut-off 20, 5 mm for TAPSE with a sensibility of 80, 5% and specificity of 78, 8%; cut-off 0, 62 for TAPSE/sPAP ratio with a sensibility of 85, 4% and a specificity 81, 8%). At Kaplan-Meier estimation, the TAPSE/sPAP ratio showed a significantly reduced survival in the lowest interquartile ranges. Moreover, at multivariate analysis TAPSE/sPAP was the only independent prognostic factor (β −5, 644; 95% IC: 0, 000–0, 522; p<0, 027). Discussion: The RVAC is significantly impaired in CA compared to the LVH group but not between CA subgroups. TAPSE/sPAP proved to be a novel echocardiographic parameter useful in discriminating CA among genetic and non-genetic forms of LVH, and that also show prognostic significance. Funding Acknowledgement: Type of funding sources: None.